1999
DOI: 10.1093/ajcn/69.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Serum and urinary magnesium in young diabetic subjects in Bangladesh

Abstract: Malnutrition may not itself give rise to glucose intolerance, and serum magnesium deficiency seems to be a consequence rather than a cause of diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…17 In another study, prevalence was 42% in malnutrition related diabetes mellitus patients. 18 Conclusion From this study, it was found that hyponatraemia, hypokalaemia and hypomagnaesemia were common electrolyte imbalance in hospitalized diabetic patients. Prevalence of hyperkalaemia was less common.…”
Section: Discussionmentioning
confidence: 79%
“…17 In another study, prevalence was 42% in malnutrition related diabetes mellitus patients. 18 Conclusion From this study, it was found that hyponatraemia, hypokalaemia and hypomagnaesemia were common electrolyte imbalance in hospitalized diabetic patients. Prevalence of hyperkalaemia was less common.…”
Section: Discussionmentioning
confidence: 79%
“…So we believed that malnourishment did not interfere in PI size. In the literature on the other hand, an increase of the size of PI in experimentally obese animals 15 and a decreased size of the pancreas in malnourished children 16 has been described.…”
Section: Discussionmentioning
confidence: 99%
“…They found significantly higher urinary magnesium (30 mmol/L versus 6.3 mmol/L, p<0.05) and low serum magnesium (0.66 mmol/L versus 0.73 mmol/L, p<0.05) in patients with diabetes mellitus from pancreatic disease compared to normal individuals. 19 A recent study by Xu et al, evaluated urinary magnesium levels in patients with prediabetes, type 1 and type 2 diabetes mellitus, with different end-organ complications of diabetes. Patients with type 1 or type 2 diabetes had significantly lower serum magnesium and higher urinary magnesium excretion compared to healthy controls.…”
Section: Urinary Magnesium Loss In Patients With Diabetesmentioning
confidence: 99%